The Role of Environmental, Social, and Governance (ESG) Factors in Promoting Sustainable Social Entrepreneurship Business Models: A Systematic Literature Review (SRL) - Soeratin, Harry Z; Sari, Retna; Sakroni, Sakroni (International Journal of Economics Development Research (IJEDR), 2024)
Social entrepreneurship has emerged as an important approach to addressing the complex social and environmental challenges in today's world. Research shows that social entrepreneurship can generate positive impacts while achieving financial sustainability. However, this business faces significant obstacles, including economic uncertainty, environmental changes, and social dynamics. Experts emphasize the need for social entrepreneurs to deeply understand their business environment and adjust their strategies accordingly. A systematic literature review can help entrepreneurs identify the factors that influence their success and inspire innovative solutions. The main findings indicate that environmental, social, and governance factors significantly influence success, with government regulations and stakeholder interactions playing important roles. Social entrepreneurs face challenges from market uncertainty and competition, which require adaptive and innovative strategies such as operational flexibility and the use of technology. In addition, these findings underscore the need for supportive public policies to enhance the social entrepreneurship ecosystem. To support the growth and sustainability of social entrepreneurship, several key recommendations have been proposed. First, encouraging collaboration and networking among social entrepreneurs, the government, the private sector, and civil society is crucial for building support and reducing risk. In addition, enhancing capacity development and risk management programs will better equip social entrepreneurs to tackle complex challenges. Encouraging technological innovation through investment in digitalization can enhance efficiency and access to services. Regulatory reform is needed to create a stable environment while improving access to appropriate funding options will further support social entrepreneurs in making a positive impact on their communities.